Deletion of ADORA2B from myeloid cells dampens lung fibrosis and pulmonary hypertension. Issue 1 (15th October 2014) - Karmouty‐Quintana, Harry; Philip, Kemly; Acero, Luis F.; Chen, Ning‐Yuan; Weng, Tingting; Molina, Jose G.; Luo, Fayong; Davies, Jonathan; Le, Ngoc‐Bao; Bunge, Isabelle; Volcik, Kelly A.; Le, Thanh‐Thuy T.; et al.
Abstract : Idiopathic pulmonary fibrosis (IPF) is a lethal, fibroproliferative disease. Pulmonary hypertension (PH) can develop secondary to IPF and increase mortality. Alternatively, activated macrophages (AAMs) contribute to the pathogenesis of both IPF and PH. Here we hypothesized that adenosine signaling through the ADORA2B on AAMs impacts the progression of these disorders and that conditional deletion of ADORA2B on myeloid cells would have a beneficial effect in a model of these diseases. Conditional knockout mice lacking ADORA2B on myeloid cells (Adora2B f/f ‐LysM Cre ) were exposed to the fibrotic agent bleomycin (BLM; 0.035 U/g body weight, i.p.). At 14, 17, 21, 25, or 33 d after exposure, SpO2, bronchoalveolar lavage fluid (BALF), and histologic analyses were performed. On day 33, lung function and cardiovascular analyses were determined. Markers for AAM and mediators of fibrosis and PH were assessed. Adora2B f/f ‐LysM Cre mice presented with attenuated fibrosis, improved lung function, and no evidence of PH compared with control mice exposed to BLM. These findings were accompanied by reduced expression of CD206 and arginase‐1, markers for AAMs. A 10‐fold reduction in IL‐6 and a 5‐fold decrease in hyaluronan, both linked to lung fibrosis and PH, were also observed. These data suggest that activation of the ADORA2B on macrophages plays an active role in the pathogenesis of lung fibrosis and PH.‐Karmouty‐Quintana, H., Philip, K., Acero, L. F., Chen, N.‐Y., Weng, T., Molina, J. G., Luo, F., Davies, J., Le, N.‐B., Bunge, I., Volcik, K. A., Le, T.‐T. T., Johnston, R. A., Xia, Y., Eltzschig, H. K., Blackburn, M. R. Deletion of ADORA2B from myeloid cells dampens lung fibrosis and pulmonary hypertension. FASEB J. 29, 50–60 (2015). www.fasebj.org